Macroinvertebrados em córregos de baixa ordem sob diferentes usos do solo no estado de São Paulo: subsídios para o biomonitoramento - Suriano, Marcia Thais (2008)
The environmental monitoring assesses the state of preservation of aquatic ecosystems, providing information for the development of strategies for management, conservation of natural areas and plans for recovery of degraded environments. This evaluation is performed through abiotic and biotic information, in particular the macroinvertebrates. This work focused on this biota to evaluate the environmental quality of low order streams in the State of Sao Paulo using two approaches: the community structure and the selection of multimetrics. The first approach presents the study of the taxonomic composition and the structure of functional feeding groups of benthic macroinvertebrates, and the second concerns the selection of metrics applied to this community to assess the integrity of lotic environments. We selected 29 streams of 1st and 2nd orders in different landscape and land uses, of which 15 streams are located in the following Conservation Units: Parque Estadual de Campos do Jordão, Estação Ecológica de Caetetus, Parque Estadual Furnas do Bom Jesus, Parque Estadual de Vassununga, Parque Estadual do Morro do Diabo e Parque Estadual de Intervales, and 14 are located in regions with sugar cane, eucalyptus and pasture monocultures. The environmental characterization followed the protocol proposed by the Project Biota/Fapesp and is detailed in Material and Methods. In each stream we delimited a segment of 100m and took six samples of benthic fauna using a Surber sampler. The identification was made until the lowest practical taxonomic level using keys for identification, original descriptions and help of experts when needed. For the first approach, the results showed differences in the taxonomic composition and structure of functional feeding groups among the streams and the areas with different land uses. In general, there was greater participation of Trichoptera, Ephemeroptera, Plecoptera and Coleoptera in streams located in the Conservation Units and greater participation of Odonata, Diptera, Bivalvia and Gastropoda in streams located in impacted areas. The analyses of the functional feeding structure showed that the shredders were major participatants in areas with riparian vegetation including two streams located in eucalyptus monoculture. To assess the integrity of low order streams in the State of Sao Paulo we selected 51 metrics which were analyzed using the following criteria: i, predictable response to the anthropic impacts, ii, higher taxonomic resolution, iii, operational and theoretical simplicity. Eighteen metric were related to the environmental and spacial predictors used. Of these, eight metrics covered the selection criteria set and were potentially considered to integrate a multimetric system for evaluating low order streams of the State of Sao Paulo: taxonomic richness of family, total of richness Ephemeroptera, Plecoptera and Trichoptera, total density of specimens, percentage of Megaloptera and Hirudinea groups, percentage of Ephemeroptera, Plecoptera and Trichoptera groups together, the Shannon diversity index for genera and the adapted BMWP index.